Effect of different feeding levels in the dry period on pre- and post- partum serum biochemistry of crossbred dairy cows - Panigrahi, B; Pandey, H N; Pattanaik, A K (The Indian Journal of Animal Sciences, 2011)
The pre- and post-partum metabolic profiles of crossbred dairy cows (24) as influenced by 3 different prepartum feeding managements were assessed. The dietary treatments included feeding of either 3.0 kg concentrate/head/d throughout the 60d pre-partum (Tt ), or 3.0 kg concentrate during 60-22d pre-partum and thereafter at an increased allowance @ 0.25 kg/d during the next 21 d till it reached 1% of live weight (T2). The third group of cows were fed similar to T2, except that the concentrate feeding during 60-22d pre-partum was reduced to 2.0 kg (TJ All the groups had access to ad lib. green fodder throughout. The serum glucose concentration was higher in T] during early dry period in comparison to the other 2 groups. Likewise, serum urea level in T2 animals was significantly higher compared to corresponding values for T] and T3 during the early lactation stage. However, no other biochemical constituents measured were influenced by the prepartum dietary treatments during either of the 2 phases. It is concluded that the variations in pre-partum dietary management used in the present study, imparted no significant influence on the clinical biochemistry of the crossbred cows.